Flexible use of residential heat pumps: Possibilities and limits of market participation - Jessica Raasch (University of Duisburg-Essen, House of Energy Markets & Finance, 2018)
The increased amount of electricity supply from intermittent renewable energy sources leads more and more to high price volatility in electricity spot markets. An increasing share of generation is less dispatchable than in the past, and therefore higher amounts of flexible demand, which can be adjusted towards supply, are required. Even residential consumers are potential market participants, if the smart equipment of buildings and the electricity grid are readily available. This paper investigates the possibility for heat-pump operators to participate in spot markets. Especially problems and possible benefits are investigated when uncertainties in ambient temperatures or prices are considered. Therefore an optimization model, including an air-to-water heat pump, a storage tank and the heated building is implemented in MATLAB. In order to investigate the heat-pumps operation according to optimized heat-supply schedules. Along different scenarios, an agent-based model is used. Namely operations with day-ahead and intraday market participation are investigated, using historical EPEX spot electricity prices for 2014. Results show that uncertainty is a critical issue when private consumers participate in electricity markets. Even with a certain amount of system flexibility, there are tight operational constraints for the heating device, which are hard to fulfill. Short-term decisions including responses to current information are required. The system behavior is acceptable with very shortterm decision making, namely a hourly reoptimization with intraday-market participation. Further on, benefits can be yielded, when a combination of procurement before (day-ahead) and adjustments in the very short term (intraday) are applied.
Keywords: 330; Heat-Pump Operation; Flexible Consumption; Residential Market Participation; Spot-Market Bidding